2006
DOI: 10.1111/j.1530-0277.2006.00236.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mineralocorticoid and Glucocorticoid Receptor Blockade on Hypothalamic–Pituitary–Adrenal Function in Female Rats Prenatally Exposed to Ethanol

Abstract: E females showed enhanced HPA responses to both MR and GR blockade compared with PF and C before restraint as well as a different pattern of responsivity during and following restraint. While receptor blockade had some effect on CORT responses in PF females, changes in ACTH appear specific to ethanol. These findings suggest that the balance between HPA drive and feedback may be altered in E compared with C females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 37 publications
7
12
0
Order By: Relevance
“…1B). These results demonstrate that corticosteroid receptor antagonists have no significant effect on CSD-induced adrenocortical activation, a result similar to those reported previously (Glavas et al, 2006; Moldow et al, 2005; Pace and Spencer, 2005; Weidenfeld and Feldman, 1993). Taken together, the present results suggest that both MRs and GRs did not play an important role in mediating suppressive effects of glucocorticoids on HPA axis function in the intense stimuli like CSD.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…1B). These results demonstrate that corticosteroid receptor antagonists have no significant effect on CSD-induced adrenocortical activation, a result similar to those reported previously (Glavas et al, 2006; Moldow et al, 2005; Pace and Spencer, 2005; Weidenfeld and Feldman, 1993). Taken together, the present results suggest that both MRs and GRs did not play an important role in mediating suppressive effects of glucocorticoids on HPA axis function in the intense stimuli like CSD.…”
Section: Discussionsupporting
confidence: 92%
“…For example, stress-induced high plasma corticosterone levels were further exaggerated by treatment with either corticosteroid receptor antagonists alone or in combination (Ratka et al, 1989; Spencer et al, 1998). However, a no further change in plasma corticosterone levels was also reported in the animal stress models by similar treatments (Glavas et al, 2006; Moldow et al, 2005; Pace and Spencer, 2005; Weidenfeld and Feldman, 1993). In the present study, while plasma corticosterone levels in CSD rats treated with mifepristone or spironolactone alone were similarly increased as in CSD-alone rats, CSD rats treated with both mifepristone and spironolactone showed a lower plasma corticosterone level than that of the CSD-alone group.…”
Section: Discussionsupporting
confidence: 58%
“…This suggests an alteration in MR-mediated CORT signalling, and perhaps an altered MR/GR balance (Sliwowska et al, 2008). In addition, we found that MR and GR blockade resulted in greater ACTH release in PAE females but not males under basal or pre-stress conditions, compared to their PF and C counterparts (Glavas et al, 2006), which is consistent with what was observed by Young et al (2004) among depressed populations, as described above.…”
Section: Prenatal Alcohol Exposure and Hpa Dysregulationsupporting
confidence: 90%
“…The decreased stress-responsiveness with mifepristone treatment is consistent with a previous report by (Ratka et al, 1989) in which animals treated systemically with mifepristone prior to exposure to novel environment displayed decreased stress-responsiveness (i.e., corticosterone) compared with vehicle treated animals. However, there are other reports whereby mifepristone increases neuroendocrine responsiveness to restraint stress in females prenatally exposed to ethanol (Glavas et al, 2006). …”
Section: Discussionmentioning
confidence: 99%